2021
DOI: 10.1038/s41598-021-88043-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease is associated with bacterial translocation and a higher inflammation response in psoriatic patients

Abstract: Psoriasis and non-alcoholic fatty liver disease (NAFLD) are both inflammatory diseases. The study objective was to estimate the risk of NAFLD, non-alcoholic steatohepatitis, and liver fibrosis (by liver stiffness and liver biopsy) in patients with psoriasis and to determine the epidemiological, clinical, immunological (TNF-α, IL-2, IL-6, IL-12, IL-17, IL-23, and TGF-β) characteristics, and bacterial translocation. Of the 215 psoriatic patients included, 91 presented NAFLD (prevalence: 42.3%). Compared to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…8,13,14 NAFLD has been shown to occur 1.5 to 3 times more frequently in patients with psoriasis than in the general population. 3,11,15 Prevalences of NAFLD ranging up to 65% have been reported in this patient population. 16 The increased risk of NAFLD in psoriasis patients is not surprising, as the two diseases share a common link with the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…8,13,14 NAFLD has been shown to occur 1.5 to 3 times more frequently in patients with psoriasis than in the general population. 3,11,15 Prevalences of NAFLD ranging up to 65% have been reported in this patient population. 16 The increased risk of NAFLD in psoriasis patients is not surprising, as the two diseases share a common link with the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 69%
“… 65 As acitretin frequently causes hyperlipidemia, use is preferably avoided in patients with or at high risk of NAFLD. 11 , 75 , 79 , 80…”
Section: Hepatic Effects Of Systemic Psoriasis Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells also modify the physical properties of their extracellular spaces by collagen deposition. Fibrosis increases the stiffness of the extracellular space [ 24 ] and the intensity of this process may modify the rigidity of the cell environment. Similarly, Col1A1 gene expression was found to be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported more than 40% prevalence of MAFLD in a cohort of more than two hundred psoriatic patients, higher than the prevalence described in the general population. This rate was found to be also associated with a higher prevalence of bacterial translocation and a higher pro-inflammatory state, evaluated by increased serum levels of TNF-α and transforming growth factor-beta (TGF-β) ( 97 ). Finally, it has been reported that psoriasis plus MAFLD confers a higher risk of developing cardiovascular disease at 10 years compared to psoriasis alone ( 98 ).…”
Section: Immune-mediated Diseases and Mafldmentioning
confidence: 99%